The craniofacial anthropometric measurement in a population of normal newborns of Kolkata - Ghosh, Anasuya; Manjari, C; Mahapatra, S (Nepal Journal of Medical Sciences, 2013)
Background: The anthropometric measurement of the craniofacial region plays an important role in the evaluation of the newborn with dysmorphic features and their corrective surgery. This study was undertaken to establish a baseline craniofacial dataset for the newborn population of Kolkata where it is still lacking. Methods: In this study, we obtained the measurement of 6 distinct parameters (length of nose, height of nose, width of columella, length of philtrum, width of philtrum, oral commissural distance) of craniofacial region of 1860 healthy newborns (both male & female). Their body weight was recorded. We compared the values in both sexes and also in normal & low birth weight babies. Results: Our study shows statistically significant higher values in all parameters except oral commissural distance among male than female newborn. It again results statistically significant higher values of length of nose, length of philtrum and oral commissural distance in normal birth weight newborns than the low birth weight group in both sexes. Conclusion: We here present a set of reference value for the newborn population (both normal & low birth weight) of East India (Kolkata). Nepal Journal of Medical Sciences | Volume 02 | Number 02 | July-December 2013 | Page 125-129 DOI: http://dx.doi.org/10.3126/njms.v2i2.8955